2018
DOI: 10.1021/acssynbio.8b00392
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis of Novel Statins by Combining Heterologous Genes from Xylaria and Aspergillus

Abstract: For many secondary metabolites, heterologous synthesis is the definitive step to determine their required biosynthetic genes. Using a multivector expression system in Saccharomyces cerevisiae, we reconstituted not only two natural statins from two fungal species, i.e., lovastatin from Aspergillus terreus and FR901512 from Xylaria grammica, but also new statin structures by mixing their genes. Combinatorial gene exchange experiments revealed the functional promiscuity of two polyketide synthases in A. terreus, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Within the same work reporting on a multitude of new terpenoids from a species potentially representing H. fendleri (see Terpenoids section), several terphenyls were reported [89]. Apart from rickenyls C-E known from H. rickii [98], four new terphenyls named fendleryls A (69) to D were isolated [89]. Fendleryls A−D exhibited no antimicrobial activity, but weak cytotoxicity against NCI-H187 and Vero cells with IC 50 values of 48 and 49 µM, respectively.…”
Section: Benzenoids and Lactones From Xylariaceae (Fig 7)mentioning
confidence: 97%
See 1 more Smart Citation
“…Within the same work reporting on a multitude of new terpenoids from a species potentially representing H. fendleri (see Terpenoids section), several terphenyls were reported [89]. Apart from rickenyls C-E known from H. rickii [98], four new terphenyls named fendleryls A (69) to D were isolated [89]. Fendleryls A−D exhibited no antimicrobial activity, but weak cytotoxicity against NCI-H187 and Vero cells with IC 50 values of 48 and 49 µM, respectively.…”
Section: Benzenoids and Lactones From Xylariaceae (Fig 7)mentioning
confidence: 97%
“…Another approach to attain novel natural products is heterologous gene expression. Recently, this concept has been utilized by mixing genes responsible for production of the potent statins (of which lovastatin is the most famous representative) from two producing organisms, Aspergillus terreus and X. grammica, in Saccharomyces cerevisiae [69]. This ultimately resulted in MS/MS predictions of two novel structures, O-acetylmonacolin J and "methylbutyryl DA_FR901512".…”
Section: Benzenoids and Lactones From Xylariaceae (Fig 7)mentioning
confidence: 99%
“…Moreover, the binding is also determined by the compound structure; e.g., the base structure of synthetic statins (i.e., cerivastatin, fluvastatin, atorvastatin, and rosuvastatin) containing fluorinated phenol groups provides additional sites for enzyme binding. Nevertheless, the differences in the structure are thought to impact statins’ bioactivity, determining their medical values, while the mechanistic relationship between medicinal properties and core structure has not been elucidated [ 61 ]. Evaluation of the crystal structures of the statin-enzyme complex showed that statins bind with HMGR with a large number of van der Waals forces.…”
Section: Mechanism Of Actionmentioning
confidence: 99%
“…[1] Thus, a previous research focused on heterologous genes combination for novel statin biosynthesis. [2] Another work explored the substrate scope of wild-type acyltransferase LovD, which naturally acylates Monacolin J acid (MJA) to yield lovastatin aided by an acyl carrier protein (LovF-ACP). [3] Synthetic surrogates, such as acyl-CoA, N-acetyl cysteamine (SNAC) and methyl thioglycolate (SMTG) thioesters were successfully used as acyl donors, substituting the S-acyl-LovF native ACP.…”
Section: Introductionmentioning
confidence: 99%
“…These compounds, which belong to the family of statins, entail a big pharmaceutical value as cholesterol‐lowering drugs since they inhibit hydroxy methyl glutaryl coenzyme A (HMG‐CoA) reductase [1] . Thus, a previous research focused on heterologous genes combination for novel statin biosynthesis [2] . Another work explored the substrate scope of wild‐type acyltransferase LovD, which naturally acylates Monacolin J acid (MJA) to yield lovastatin aided by an acyl carrier protein (LovF‐ACP) [3] .…”
Section: Introductionmentioning
confidence: 99%